ANALISIS PENGGUNAAN BAHASA JAKSEL PADA VIDEO BERJUDUL ‘LANGUAGE BARRIERS, CULTURE SHOCK & TCK IDENTITY CRISIS FT. MELLA CARLI’ DI YOUTUBE: KAJIAN SOSIOLINGUISTIK CAMPUR KODE - Mustikawati, Widhi; Kundharu Saddhono (BASA Journal of Language & Literature, 2024)
In the video "Language Barriers, Culture Shock &; TCK Identity Crisis ft. Mella Carli" on the YouTube channel "The Indah G Show," the use of the Jaksel (South Jakarta) language in sociolinguistic contexts is examined in this article. In order to comprehend how the host, Indah G, and her invited guest, Mella Carli, utilize Jaksel language in their interactions, this study employs a code-mixed sociolinguistic study approach. Analysis of the video's conversational content and transcription are part of the research methodology. The examination's findings demonstrated that Jaksel frequently utilized his language in casual talks, jokes, and professions of respect. In other cases where formality or clarity are required, mixed code using standard Indonesian is used. Identifying the social and cultural elements that support the usage of Jaksel language in this setting is another goal of this study.